PERBEDAAN TINGKAT KEPUASAN PASIEN BPJS DAN NON BPJS TERHADAP PELAYANAN PENDAFTARAN DI RSUD TOBELO - Bitjoli, Vivia Ozora; Pinontoan, Odi; Buanasari, Andi (Universitas Sam Ratulangi, 2019)
Abstrack :Patient satisfaction level is considered as one of the very important dimension and is oneof the main indicators of the standard of a health facility which is due to the influence of health careon the hospital and it is this which makes the measurement of patient satisfaction is an importantcomponent.The purpose of this study was to determine the differences between patient satisfactionlevel on BPJS and Non BPJS users over registration services in Tobelo hospitals. This researchmethod using cross sectional design. The sampling technique used consecutive sampling techniquewith a total sample of 136 respondents. methods of data collection using questionnaires satisfactionlevel of service at the place of registration to measure the level of patient satisfaction BPJS and NonBPJS and statistical test using chi square test. The researchresults can be p-value of 0.000 (â‰¤ Î± =0.05), which means there are significant differences. Conclusion there are differences between thelevel of patient satisfaction level on BPJS and Non BPJS users over registration services in Tobelohospitals.Keywords: Enrollment Services, BPJS patient and the Non BPJS, SatisfactionAbstrak : Tingkat kepuasan pasien dianggap sebagai salah satu dimensi yang sangat penting danmerupakan salah satu indikator utama dari standar suatu fasilitas kesehatan yang merupakan akibatpengaruh pelayanan kesehatan atas pihak rumah sakit dan hal inilah yang membuat pengukurankepuasan pasien menjadi komponen penting. Tujuan penelitian ini adalah untuk mengetahuiperbedaan tingkat kepuasan pasien BPJS dan Non BPJS terhadap pelayanan pendaftaran di RSUDTobelo. Metodepenelitian ini menggunakan desain cross sectional. Teknik pengambilan sampelmenggunakan teknik consecutive sampling dengan jumlah sampel sebanyak 136 responden. metodepengumpulan data menggunakan kuesioner tingkat kepuasan pelayanan di tempat pendaftaran untukmengukur tingkat kepuasan pasien BPJS dan Non BPJS dan uji statistic menggunakan uji chi square.Hasil penelitian di dapat nilai p-value sebesar 0,000 (â‰¤ Î± = 0,05) yang berarti ada perbedaan yangsignifikan. Kesimpulan ada perbedaan antara tingkat kepuasan pasien BPJS dan Non BPJS terhadappelayanan pendaftaran di RSUD Tobelo.Kata kunci : Pelayanan Pendaftaran, pasien BPJS dan Non BPJS, Tingkat Kepuasan